The Influence of Educational Videos on Knowledge of Food and Beverage Consumption of Contemporary Snacks in Young Women at SMA PGRI 2 Palembang - Ravi Masitah; Rio Purnama (IKesT Muhammadiyah Palembang, 2023)
Introduction: Consumption of snack foods and drinks contributes to adolescent intake which affects nutritional status so good knowledge is needed. Educational videos are an interesting nutrition education medium and can help increase nutrition knowledge in adolescents. This study aims to determine the influence of educational videos on knowledge of food consumption and beverages of contemporary snacks in adolescent girls at SMA PGRI 02 Palembang. Method: This research is a quasi-experiment with one group pretest posttest group design. The study was conducted at SMA PGRI 02 Palembang in March. The study sample was 106 students according to inclusion and exclusion criteria. The statistical test used is the paired sample t test. Results: There is a significant difference in educational videos on the knowledge of food consumption and contemporary snack drinks for young women at SMA 02 PGRI Palembang after being given educational videos with a p value of <0.05. Conclusion: Interesting educational videos can increase teenagers' attention to the material presented so that it can change the knowledge of food consumption and snack drinks for the better.